Characteristics of granular activated carbon from UTM pilot plant - Mulop, Normah; Abdul Aziz, Ramlan; Ku Hamid, Ku Halim (1991)
The granular activated carbon is produced from coconut shell. The pilot plant initially carbonizes the raw coconut shell to produce charcoal. The crushed charcoal is then converted to activated carbon. Factors that are affecting the activation process such as time of activation and size of particles forming the bed are varied. The characteristics of the activated carbon produced are determined by using standard tests and a scanning electron microscope is used to determine the surface structures. The results show that the pilot plant is able to produce a good quality activated carbon from agricultural waste.